The Effectiveness of Using Word Adventure Game in Improving Students’ English Vocabulary Mastery in Fifth-Grade at MI Hidayatussibyan Lancar - Novi Nur Hidayati; Zulfa Nabila (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Students often face difficulties mastering English vocabulary due to conventional rote memorization and passive learning, a problem also observed among fifth-graders at MI Hidayatussibyan Lancar. This study aims to investigate the effectiveness of using the Word Adventure Game in improving students' English vocabulary mastery. Utilizing a quantitative approach with a quasi-experimental non-equivalent pretest-posttest control group design, two intact classes were selected via purposive sampling: an experimental group taught using the game and a control group taught through conventional methods. The research instrument was a validated vocabulary mastery test based on the topic